The divide between us: internet access among people with and without disabilities in the post-pandemic era. - Pacheco, Edgar; Burgess, Hannah (Disability & Society, 2025)
The COVID-19 pandemic highlighted the importance of internet access across various aspects of life, from remote work and online education to healthcare services and social connections. As we transition to a post-pandemic era, a pressing need arises to update our understanding of the multifaceted nature of internet access. This study is one of the first attempts to do so. Using survey data from New Zealand adult internet users (n = 960), it compares internet connection types, frequency of internet use at home, social media use, and concerns about online risk between people with and without disabilities. Results show people with disabilities have restricted fibre access and higher wireless broadband (a much slower connection type). People with disabilities use social media platforms less and are more concerned about certain online risks. The findings highlight persistent disparities in internet access for people with disabilities in the post-pandemic era. Implications of the study are discussed. Points of interest: The study explores internet access and compares trends between people with and without disabilities from New Zealand in the aftermaths of the pandemic. Internet access is investigated in terms of its frequency of use at home, type of internet connection, frequency of social media use, and perceptions about the benefits of the internet as well as concerns related to online risks. The data indicate that inequities in internet access exist. A disability broadband divide has been identified, with disabled people having less access to faster internet connections than non-disabled people. There were significant differences in the frequency with which people with and without disabilities used the internet at home and used prominent social media sites. People with disabilities are also more concerned about internet threats like conspiracy theories and hate speech.